Applications of Bioadhesives: A Mini Review - Duan, Wanglin; Bian, Xiangbing; Bu, Yazhong (Frontiers in Bioengineering and Biotechnology, 2021)
Bioadhesives have demonstrated their superiority in clinical applications as tissue adhesives, hemostats, and tissue sealants. Because of the intrinsic stickiness, the applications have been expanded to various areas, such as functional wound dressing, factors delivery vehicles, and even medical devices fixation. While much literature discussed the mechanism of bioadhesives, few of them specifically summarized the applications of bioadhesives. To fill in the blanks, this review covers recent research papers and focuses precisely on the applications of bioadhesives, which can be generally classified as follows: 1) wound closure, 2) sealing leakage, and 3) immobilization, including those already in the clinic and those showing great potential in the clinic. It is expected that this paper will provide a whole picture for bioadhesives' applications and lead to innovations in applying bioadhesives in new fields.